Unusual Cause of Persistent Epistaxis with Severe Anemia in a Child - Yilkal Zemene; Tadele Hailu; Josh Wiedermann (Case Reports in Otolaryngology)
Epistaxis in children can be caused by different systemic and local pathologies. Respiratory infections, nasal mucosa dryness, and foreign bodies are some local causes of bleeding from the nose. In developing countries, infestations still contribute a significant proportion of anemia in children. But it is very unusual for leech-causing persistent epistaxis with a consequence of severe anemia. We herein report a rare cause of severe anemia in a 5-year-old child presented to our clinic for persistent epistaxis. A leech was taken out with forceps, and his anemia was treated accordingly.